Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1097-4636(19991215)47:4<585::aid-jbm16>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Early events associated with periodontal connective tissue attachment formation on titanium and hydroxyapatite surfaces

Abstract: Endosseous dental implants can support at least three types of biomaterial/connective tissue interfaces: osseointegration, fibro-osseous integration, and periodontal connective tissue attachment. Although a periodontal connective tissue attachment offers distinct advantages, only osseointegration and fibro-osseous integration are at present clinically achievable. Recent studies indicate a periodontal regeneration-competent cell population and an appropriate biomaterial substrate both are required for periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Amino groups in addition to the intact HA surface may influence initial cell adhesion and growth on HA/silicone. The cell‐growth curve for HA/silicone was delayed compared to that of cell culture plastic, the positive control, and finally reached the same level statistically for 72 h. Craig and LeGeros reported levels of HPLF proliferation, and collagen and noncollagen protein synthesis for cells grown on the HA‐coated surface lagged behind cells cultured on the cell‐culture plate 25. This may be because biomaterial substrates depend on the temporal sequence of extracellular matrix proteins associated with periodontal connective tissue attachment, and surface properties such as topography.…”
Section: Discussionmentioning
confidence: 96%
“…Amino groups in addition to the intact HA surface may influence initial cell adhesion and growth on HA/silicone. The cell‐growth curve for HA/silicone was delayed compared to that of cell culture plastic, the positive control, and finally reached the same level statistically for 72 h. Craig and LeGeros reported levels of HPLF proliferation, and collagen and noncollagen protein synthesis for cells grown on the HA‐coated surface lagged behind cells cultured on the cell‐culture plate 25. This may be because biomaterial substrates depend on the temporal sequence of extracellular matrix proteins associated with periodontal connective tissue attachment, and surface properties such as topography.…”
Section: Discussionmentioning
confidence: 96%
“…15 We had previously reported that primary cell cultures of rat PDL but not GCT expressed a cementum-associated extracellu- lar matrix protein when cultured on tissue culture plastic or titanium. 8 However, when cultured on amalgam, calcium hydroxide, or gutta percha surfaces, primary PDL cells failed to express the cementum-associated protein. 7 These results reflect, in part, the response of the PDL to these materials in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a cementumassociated extracellular matrix protein, CP42, was determined by a dot blot assay as previously described. 8 Immediately before implant placement, both PDL and GCT cells were released from culture by treatment with trypsin-EDTA and counted. The cells, at a concentration of 4 3 10 6 cells/mL, were transferred to the surgical site in a vehicle of 3% gelatin in DMEM-F12 medium without serum in a tuberculin syringe on ice.…”
Section: Establishment Of Primary Periodontal Cell Culturesmentioning
confidence: 99%
“…This type of sealing could prolong the life of restorations by eliminating secondary caries and micropenetration of oral bacteria [15]. It has been observed that when composite is inserted into a cavity and bonded into more than one dentinal wall, the tooth-bond interface goes into contraction stresses that can exceed the bond strength and may lead to a separation.…”
Section: Introductionmentioning
confidence: 99%